1982
DOI: 10.1002/er.4440060302
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of ammonia-water absorption cycles for refrigeration and space conditioning systems

Abstract: This paper presents an investigation of an ammonia‐water absorption cycle for solar refrigeration, airconditioning and heat pump operations at higher heat supply temperatures. The system consists of a solar driven generator, rectifier, condenser, evaporator, absorber and heat exchangers for preheating and subcooling within the system. A steady state thermodynamic cycle analysis based on mass and heat balances along with the state equations for the thermodynamic properties of the ammonia‐water mixture has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Since the results of the above works indicate that the operating conditions of the generator such as temperature, pressure and mass flow rates of water and ammonia play a major role in determining the COPs of the whole cycle (which can be controlled by the governing operating principles of distillation towers), it reminds us that the generator of the cycle may be replaced by a distillation tower. This idea was first innovated by Kaushik and Bhardwaj [11] who added a rectifier on the top of generator. From the results of their theoretical analysis, they found that an increase of condenser temperature can improve the performance of the cycle at higher generator temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the results of the above works indicate that the operating conditions of the generator such as temperature, pressure and mass flow rates of water and ammonia play a major role in determining the COPs of the whole cycle (which can be controlled by the governing operating principles of distillation towers), it reminds us that the generator of the cycle may be replaced by a distillation tower. This idea was first innovated by Kaushik and Bhardwaj [11] who added a rectifier on the top of generator. From the results of their theoretical analysis, they found that an increase of condenser temperature can improve the performance of the cycle at higher generator temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of absorption cycles for refrigeration and air-conditioning applications is quite well established in the available literature (Ellington et al, 1957;Ward, 1979;Allen et al, 1976;Auh, 1977;Kaushik, undated;Kaushik and Bhardwaj, 1982). Both the water-LiBr and NH,-H20 combinations as refrigerant-absorbent pairs have been widely used by many investigators.…”
Section: Introductionmentioning
confidence: 99%